Antagonistic effect of Trichoderma spp. on Ustilago segetum var. tritici and their compatibility with fungicides and biocides - and R. AGGARWAL, GOUTAM MONDAL, K.D. SRIVASTAVA (Indian Phytopathology, 2002)
Max. inhibitory effect on germination of chlamydospores of the wheat pathogen U. segetum var. tritici was obtained in vitro with culture filtrate of T. viride (TV-5) followed by T. koningii, T. hamatum, T. harzianum and T. lignorum [T. viride]. Antifungal compounds extracted from T. viride (TV-5) followed by T. koningii also suppressed mycelial growth of the host pathogen in liquid medium. T. koningii, T. harzianum and T. lignorum were compatible with carboxin at 200 and 500 p.p.m. Although neem oil and antifeedant neem formulations showed compatibility with all 6 isolates of Trichoderma but none had antifungal activity against the loose smut pathogen at 100 p.p.m. except neem oil at 250 p.p.m.